Production and characterisation of lipase for application in detergent industry from a novel Pseudomonas helmanticensis HS6. (August 2020) - Phukon, Loreni Chiring; Chourasia, Rounak; Kumari, Megha; Godan, Tharangattumana Krishnan; Sahoo, Dinabandhu; Parameswaran, Binod; Rai, Amit Kumar
Highlights: P. helmanticensis lipase was purified and characterized for the first time. Statistical optimization enhanced lipase activity from 2.3 to 179.3 U/mg. Partially purified lipase is active in temperature (5–80 °C) and pH (6–9) range. Lipase is stable in commercial detergents at 5 °C and 30 °C. Lipase from P. helmanticensis can be applied in detergent industry. Abstract: The aim of this study was to explore novel source of lipase from biodiversity hot spot region of Sikkim with activity at broad temperature range for application in detergent industry. Among the isolates, Pseudomonas helmanticensis HS6 showed activity at wide range of temperatures was selected for lipase production. Statistical optimisation for enhanced production of lipase resulted in enhancement of lipase activity from 2.3 to 179.3 U/mg. Lipase was purified resulting in 18.78 fold purification, 5.58% yield and high specific activity of 3368 U/mg. The partially purified lipase was found to be active in wide range of temperature (5–80 °C) and pH (6–9), showing optimum activity at 50 °C at pH 7. Peptide sequences on mass spectrometric analysis of purified lipase showed similarity to lipase family protein of three species of Pseudomonas. Both crude and purified lipase retained residual activity of 40–80% after 3 h of incubation with commercial detergents suggesting its application in detergent industry.